2020
DOI: 10.1055/s-0040-1708037
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Proximal Tibia Periprosthetic Fractures in Primary Total Knee Arthroplasty

Abstract: Intraoperative fracture of the proximal tibia is a rare complication of total knee arthroplasty (TKA) with few studies available reporting risk factors or prognosis. A review of our prospective joint registry was performed to determine the incidence and associated risk factors of intraoperative tibia fractures during primary TKA; 14,966 TKAs of all manufacturers were performed with 9 intraoperative tibia fractures. All fractures occurred in a single TKA design. There were 8,155 TKAs of this design performed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Most post-operative traumatic peri-prosthetic fractures involve the femur 22 . Intra-operative fractures in primary arthroplasty are mostly of metaphyseal origin and most frequently affect the metaphyseal femur 4 , 7 , 23 . In contrast, fractures during revision arthroplasty occur more frequently on the tibial side and most frequently on the diaphyseal side 11 , 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most post-operative traumatic peri-prosthetic fractures involve the femur 22 . Intra-operative fractures in primary arthroplasty are mostly of metaphyseal origin and most frequently affect the metaphyseal femur 4 , 7 , 23 . In contrast, fractures during revision arthroplasty occur more frequently on the tibial side and most frequently on the diaphyseal side 11 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Die meisten postoperativen traumatischen periprothetischen Frakturen betreffen das Femur 22 . Die intraoperativen Frakturen in der Primärendoprothetik sind meist metaphysär lokalisiert und betreffen ebenfalls am häufigsten das metaphysäre Femur 4 , 7 , 23 . Demgegenüber treten Frakturen in der Revisionsendoprothetik häufiger tibialseitig auf und dabei am häufigsten diaphysär 11 , 21 .…”
Section: Diskussionunclassified
“…13 Tibia Tibial baseplates with greater keel size relative to their medial-lateral size increases risk for plateau fracture. 5,14 This may be attributed to the increased proximity of the keel cut to the cortex. 14 Damsgaard et al 14 reported that utilization of larger thickness polyethylene ($13 mm) from deeper tibial resection was associated with a decreased fracture risk.…”
Section: Implant Femurmentioning
confidence: 99%
“…5,14 This may be attributed to the increased proximity of the keel cut to the cortex. 14 Damsgaard et al 14 reported that utilization of larger thickness polyethylene ($13 mm) from deeper tibial resection was associated with a decreased fracture risk. The authors suggested that thicker tibial resection removed weaker, sclerotic subchondral bone and allowed the tibial baseplate to rest on a stronger metaphyseal undersurface.…”
Section: Implant Femurmentioning
confidence: 99%
“…If the fracture is recognized and treated correctly intra-operatively, there is no difference in post-operative rehabilitation compared to a normal primary or revision knee replacement. 6 , 33 , 40 , 41 In case of unstable type IC fractures, a secure option may be screw fixation and implant of a long-stemmed tibial component that bridges the fracture engaging the distal diaphysis and enhances fixation. In case of type IIC, a long-stemmed tibial component can be used while bone grafting the fracture site.…”
Section: Introductionmentioning
confidence: 99%